Tingkat Partisipasi Masyarakat pada Perencanaan Penggunaan Dana Desa dalam Rangka Pengentasan Kemiskinan di Desa Kesimantengah - Daniati, Sri (Jurnal Ilmiah Administrasi Publik, 2019)
The purpose of this study is to determine the level of community participation in planning the use of the Dana Desa in order to alleviate poverty in the Kesimantengah Village of Pacet District, Mojokerto Regency. This type of research is qualitative with triangulated data collection methods, namely a combination of interviews, observation, and documentation. While the data sources needed in this study are informants, phenomena, and documents relating to research. The measurement of the level of community participation in this study uses the Muluk participation ladder (2007). The results showed that the level of community participation in planning the use of Dana Desa in Kesimantengah Village was in the category of moderate participation, namely on the consultation steps. This was marked by the existence of a village meeting attended by elements of the community, village government and community organizations to draw up village government work plans for the following year.